Salinity Effect on the Germination and Some Chemical Components of Matricaria spp - GHANAVATI, MEHDI; SENGUL, SULEYMAN (Asian Journal of Chemistry, 2010)
Chamomilla recutita (L.) (Syn: Matricaria recutita and Matricaria chamomilla), is the most important medicinal plants. An objective of this study is to investigate the effects of salinity levels on yield and yield components in germination and growth stage of two chamomile species. The experiment completed in 2006 in the agriculture college laboratory of Shahrekord University and Isfahan Agriculture Research Center. Plants were grown in the agronomy laboratory of Shahrekord University for germination test. The treatments included salt levels of control, 6, 12 and 18 dSm-1. The genotypes were cultivated at greenhouse in sand irrigated with nutrient solutions. The salinity stress in this trial exerted at 2 durations. The first from seedlings stage (35 days after emergence with plants at 8-10 leaves) until the end of the experiment (about 3 months). The second duration of stress exertion began at stem elongation and seedlings emergence from rosette stage to harvest (about 1.5 month). This experiment carried out as a split split plot with 3 replication on the based of CRD design. The traits measured stem and root dry matter yield with stem relative water, root relative water and Na, K, and Ca content in relation to salinity effects on seedling stage and stem formation. The salt application trials indicated that dry matter yield was decreased with increasing NaCl doses. Effect of salt treatment on genotypes was decreased with increasing salt concentration in all treatments, but Na increased with increasing salt concentration either stem or root. All the criteria investigated suggest therefore that M. aurea were superior to M. recutita genotypes. Positive and highly significant relationships existed between stem dry matter yield and all its components with the exception of the stem relative water (r = 0.053). But these significance were negative in Na stem (-0.309**) and Na root (-0170**). There were also highly positive significant relationship between root dry matter yield and all its examined characters with exception of Na stem (-0.487**) and Na root (-0.218**). There was a significant difference between genotypes studied for all traits except for root relative water content. The Matricaria aurea genotypes revealed more tolerance to against salinity specially Isfahan and Mashhad genotypes.